Partisipasi Perempuan Dalam Penyusunan Reusam Perlindungan Anak Di Tingkat Gampong Di Aceh Besar - Mansari; Muslim Zainuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
Women's participation in the preparation of gampong reusam (village rules) that regulate child protection is relatively small compared to men. Whereas the participation of women has an important role so that the rules produced can represent their role. Without the involvement of women implicate the reusam that does not berperspektif gender. The research aimed to answer the problems about women's mechanism and participation in the formulation of gampong reusam in Kabupaten Aceh Besar, and the process of involvement of women in the preparation of village reusam. This empirical research was conducted in Aceh Besar District in three gampongs, namely Gampong Lambirah Kecamata Suka Makmur, Gampong Neusok Darul Kamal Subdistrict and Gampong Neuheun District Mesjid Raya. The research data was obtained through interviews with keuchik gampong, female characters and Tuha Peut Gampong. The results showed that the mechanism of compilation of reusam was done by way of deliberation in meunasah and balee (balai) pengajian by involving various elements in society, especially gampong, women and children figures also involved. Involvement of women is usually done by invited by loudspeakers in meunasah and also delivered orally by Keuchik (Village Head). The presence of women has not been maximized in the process of preparing the reusam gampong because the arrangement is done at night, time to rest, keeping the children at home, the weather is not supportive because of the rain. The role of women in the village reusam has been represented in the context of the handling of children against the law.